2007
DOI: 10.1007/s11082-007-9111-7
|View full text |Cite
|
Sign up to set email alerts
|

External cavity diode lasers with E-beam written silicon diffraction gratings

Abstract: Performance of external cavity diode lasers with silicon gratings produced by E-beam writing and subsequent reactive ion etching is described. Optical amplifiers used in the experiments were based on single quantum well heterostructures grown by molecular beam epitaxy. The lasers were set up in the Littrow configuration and have been designed to allow for wavelength tuning in the range centred at 960 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The SOA chip was attached to a thermoelectric cooler to allow for control of its temperature with the accuracy of ±0.1 K. It was oriented in such a way that the active layer plane (quantum well plane) was parallel to the grating grooves since it was already found that this is an obligatory condition for ECL operation with the broad contact SOAs due to single mode operation of the SOA in direction per− pendicular to the quantum well plane [12]. The SOA chip was pulse driven (I D = 0.4 A) with the current pulses t 2−μs long and 10−kHz repetition frequency.…”
Section: Experimental Ecl Set-upmentioning
confidence: 99%
“…The SOA chip was attached to a thermoelectric cooler to allow for control of its temperature with the accuracy of ±0.1 K. It was oriented in such a way that the active layer plane (quantum well plane) was parallel to the grating grooves since it was already found that this is an obligatory condition for ECL operation with the broad contact SOAs due to single mode operation of the SOA in direction per− pendicular to the quantum well plane [12]. The SOA chip was pulse driven (I D = 0.4 A) with the current pulses t 2−μs long and 10−kHz repetition frequency.…”
Section: Experimental Ecl Set-upmentioning
confidence: 99%
“…Profile of the grating grooves depends on the particular method used for their fabrication. The E-beam writing process combined with reactive ion eching (RIE) delivers gratings with rectangular grooves which have been found quite satisfactory for ECTL operation [49]. In addition, this method is particularly compatible with other processing operations involved in the MOEM technology since it enables pattern generation without any primary mask.…”
Section: Diffraction Gratingsmentioning
confidence: 99%
“…In 1990s ECDL systems were the essential tool for atomic physics and spectroscopy because of their wavelength tuning characteristics and narrower linewidth output. Several groups have investigated the ECDL systems to improve its critical weaknesses and they published so many reviews and articles including; simplicity of construction and compactness [9], coupling efficiency [10] and optical feedback [11], frequency selection with band-pass filters [12], transmission gratings [13], Volume Phase Holographic Grating (VPHG) [14], spectral characteristic [15] and line-width measurement [16], laser wavelength control [17] and increasing the mod-hop free running range [18].…”
Section: Introductionmentioning
confidence: 99%